Dayak Onion (Eleutherine palmifolia) Extract Reduces MSG-Induced Obesity in Mice - Rahmatullah, Aldin Akbar; Ratnaningtyas, Nurrohmah; Rahajeng, Anggreani Desi Ramadhani; Indrajaya, Putra; Firdaus, Ahmad Thoriqul; Hidayat, Rosid; Shaffirudin, Yosfiansya Fernandi; Zahli, Haikal Akmal; Irkhamy, Muhamad Naufal (Journal of Basic Medical Veterinary, 2025)
This study evaluated the anti-obesity effects of Dayak onion (Eleutherine palmifolia) extract in MSG-induced obese mice. Twenty-five male mice were divided into five groups: negative control (CMC-Na), positive control (MSG, 4 mg/g BW), and three groups receiving MSG plus Dayak onion extract at 30, 60, or 120 mg/kg BW for 52 days. Body weight was measured weekly, and abdominal fat (retroperitoneal, epididymal, peritoneal) was weighed using a digital scale on day 53. One-way ANOVA with Duncan’s post hoc test analyzed differences (p<0.05). MSG increased body weight (40.8 ± 1.1 g) and fat compared to the negative control (31.2 ± 0.5 g). Dayak onion extract dose-dependently reduced body weight (T1: 38.2 ± 0.6 g; T2: 36.0 ± 0.9 g; T3: 32.3 ± 0.6 g) and fat, with the 120 mg/kg dose nearing control levels. Flavonoids and anthraquinones in the extract likely drive these effects, suggesting Dayak onion’s potential as a natural anti-obesity agent. Human studies are needed to confirm these findings.